PROCESS IMPROVEMENT BY IMPLEMENTATION OF KAIZEN AS A QUALITY TOOL WITHIN DEFINED CONSTRAINTS: A CASE STUDY IN MANUFACTURING INDUSTRY - Sharma, Puneet; Sharma, Neeraj Kumar; Singh, M (MATTER: International Journal of Science and Technology, 2015)
Kaizen is a concept that focuses on improving a work area or an organization in incremental steps. The first well-known and most frequently cited proponent of kaizen was Imai, who wrote KAIZEN – The Key to Japan’s Competitive Success (1986. This paper illustrates about kaizen case study in Small Medium Industries (SMI) Company that is ABC Company, which produce non woven fabrics. This case study is focused on reducing material wastage. Kaizen steps are used as guidelines and PDCA Cycle is choosing as problem solving approach to conduct the case study. The properly tools and techniques such as why, Work Instruction Sheet, Pareto diagram, Process Mapping, PDCA Cycle and brainstorming were used. The kaizen implementation has reduced the of time losses More than that, sales order processing lead time and production lead time was also reduced. These results have proved the effectiveness of kaizen methodology.